Investigations on pollen production and quality in some standard pomegranate (Punica granatum L.) cultivars - Gozlekci S.; Kaynak L. (Production, processing and marketing of pomegranate in the Mediterranean region: Advances in research and technology, 2000)
In this study, the capacity of pollen germination and viability of Fellahyemez, Eksilik, Ernar, Hicaznar, Katirbasi and Asinar cultivars, which were determined after the selection studies conducted on Mediterranean pomegranates, and the amount of pollen production per flower and anther were examined. Unfertile (type A) and fertile (type B) flowers belonging to each cultivar were examined individually. While the pollen viability was determined in 2,3,5 Triphenyl Tetrazolium Chlorid (TTC), Fluorescein Diacetat (FDA) and Trypan Blue (TB) solutions by staining, the pollen germination experiments in in vitro conditions were made by using agar method in a petri dish. The pollen production capacities were determined by hemacytometric method. Results indicated that there were some differences among cultivars and between fertile and unfertile flowers of each individual cultivar in terms of pollen production, pollen germination and viability.
Symposium on 'Production, processing and marketing of pomegranate in the Mediterranean region: Advances in research and technology', 1998/10/15-17, Orihuela (Spain)